The protist community traces seasonality and mesoscale hydrographic features in the oligotrophic Sargasso Sea - Blanco-Bercial, Leocadio; Parsons, Rachel; Bolaños, Luis M.; Johnson, Rod; Giovannoni, Stephen J.; Curry, Ruth (Frontiers in Marine Science, 2022)
Protists represent the majority of the eukaryotic diversity in the oceans. They have different functions in the marine food web, playing essential roles in the biogeochemical cycles. While the available data is rich in horizontal and temporal coverage, little is known on their vertical structuring, particularly below the photic zone. The present study applies V4 18S rDNA metabarcoding to samples collected over three years in conjunction with the BATS time-series to assess marine protist communities in the epipelagic and mesopelagic zones (0-1000m). The protist community showed a dynamic seasonality in the epipelagic, responding to hydrographic yearly cycles. Mixotrophic lineages dominated throughout the year. However, autotrophs bloomed during the rapid transition between the winter mixing and the stratified summer, and heterotrophs had their peak at the end of summer, when the base of the thermocline reaches its deepest depth. Below the photic zone, the community, dominated by Rhizaria, is depth-stratified and relatively constant throughout the year, although they followed local hydrographic and biological features such as the oxygen minimum zone. The results suggest a dynamic partitioning of the water column, where the niche vertical position for each community changes throughout the year in the epipelagic, likely depending on nutrient availability, the mixed layer depth, and other hydrographic features. At depth, the protist community closely tracked mesoscale events (eddies), where the communities followed the hydrographic uplift, raising the deeper communities for hundreds of meters, and compressing the communities above.